2015
DOI: 10.1016/j.btre.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Improving the biophysical properties of anti-ricin single-domain antibodies

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…In addition, in contrast to the wildtype anti-hCG VHH, protein concentration dependencies of heat denaturation were observed in 2-SS, 1-SS and 0-SS (WA) mutants at >1 mM of protein concentration. Recently, Turner et al (38) reported the heat resistance of three different VHHs and their mutants with different charge distribution. Although the heat resistance of these VHHs was generally high, one of the wild-type VHHs was only marginally heat tolerant at 72 C. Mutations introducing more negatively charged amino acids than parental VHH improved the heat resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in contrast to the wildtype anti-hCG VHH, protein concentration dependencies of heat denaturation were observed in 2-SS, 1-SS and 0-SS (WA) mutants at >1 mM of protein concentration. Recently, Turner et al (38) reported the heat resistance of three different VHHs and their mutants with different charge distribution. Although the heat resistance of these VHHs was generally high, one of the wild-type VHHs was only marginally heat tolerant at 72 C. Mutations introducing more negatively charged amino acids than parental VHH improved the heat resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the initial on-rate has the advantage that one does not require a standard curve and thus is a simple, sensitive, and direct measure of binding activity (31). …”
Section: Analytical Techniques For Studying Sdab Stabilitymentioning
confidence: 99%
“…The wild type sequences for all but two of the sdAb prepared here have been previously published in other works (Conway et al, 2010;Richard et al, 2013;Vance et al, 2013;Liu et al, 2015;Turner et al, 2015). The sequences as produced for this work with the location of the added cysteines that formed the additional disulfide bond marked are shown in Fig.…”
Section: Reagent and Buffersmentioning
confidence: 99%
“…The sdAb were produced as previously described (Turner et al, 2015). Briefly, the PET22b plasmid carrying the sdAb gene and the pTUM4 plasmid were transformed into Tuner (DE3) for expression and grown on agar plates containing both ampicillin and chloramphenicol (100 µg/mL and 34 µg/mL respectively).…”
Section: Recombinant Protein Production and Purificationmentioning
confidence: 99%
See 1 more Smart Citation